1996
DOI: 10.1172/jci118785
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR detectable fatty acyl chain unsaturation in excised leiomyosarcoma correlate with grade and mitotic activity.

Abstract: We report on the use of 1 H-NMR two-dimensional total correlated spectroscopy (2D TOCSY) at 600 MHz for an ex vivo analysis of fatty acyl chain lipid in normal smooth muscle and a series of primary retroperitoneal leiomyosarcomas. These TOCSY spectra were used to identify and quantitate the methylene protons situated between unsaturated site protons (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 20 publications
7
34
0
Order By: Relevance
“…33 The degree of fatty acyl unsaturation is believed to be an important determinant of the metastatic potential of soft tissue sarcomas. 17 The signi cantly higher 0.9/1.3 ratio (P = 0.0001) found for tumors in our study is consistent with this. The reduction of creatine, indicative of increased energy metabolism, is also observed in both brain tumors and malignant prostate tissue.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…33 The degree of fatty acyl unsaturation is believed to be an important determinant of the metastatic potential of soft tissue sarcomas. 17 The signi cantly higher 0.9/1.3 ratio (P = 0.0001) found for tumors in our study is consistent with this. The reduction of creatine, indicative of increased energy metabolism, is also observed in both brain tumors and malignant prostate tissue.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Singer et al have shown that a signi cant correlation exists between the degree of unsaturation of fatty acyl chains, obtained from two-dimensional MRS, and the mitotic activity, indicator of grade or degree of differentiation, in soft tissue sarcomas. 17 However, such two-dimensional experiments require long acquisition times and are complicated to perform. Millis et al in their recent work used both one-and twodimensional approaches, but they limited their study to liposarcomas.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in lipid composition in mdx skeletal muscle have previously been identified in vivo and in intact biopsy samples. 68,69 Given the extensive use of genetically-modified mice, it is important to be aware of the strain background in order to fully characterize the changes induced by genetic deletion or modification. 70,71 For instance, the Fcer1g mouse comes on both a Balbc and C57BL/6J background.…”
Section: Metabonomic Studies Of Physiological Variationmentioning
confidence: 99%
“…Quantitative TOCSY was used to obtain a GPC:Cho ratio that was found to be increased in leiomyosarcomas in comparison with leiomyomas (21). It has also been used to perform lipid group analysis, showing increased fatty acyl unsaturation in leiomyosarcomas according to their mitotic activity (23), and increased fatty acyl saturation of cholesteryl ester and triglyceride in multidrug-resistant carcinoma cell lines (24). In the present study there were moderate differences in the slopes of calibration curves from one Plp derivative to another, which indicates that caution should be used when making between-derivative quantitative comparisons.…”
Section: Hrmas Proton Tocsy As a Quantitative Tool: Validation And LImentioning
confidence: 99%